2015
DOI: 10.1088/0004-637x/800/1/34
|View full text |Cite
|
Sign up to set email alerts
|

Vast Planes of Satellites in a High-Resolution Simulation of the Local Group: Comparison to Andromeda

Abstract: We search for vast planes of satellites (VPoS) in a high resolution simulation of the Local Group performed by the CLUES project, which improves significantly the resolution of former similar studies. We use a simple method for detecting planar configurations of satellites, and validate it on the known plane of M31. We implement a range of prescriptions for modelling the satellite populations, roughly reproducing the variety of recipes used in the literature, and investigate the occurence and properties of pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 57 publications
9
72
1
Order By: Relevance
“…However, the general conclusion is that planes of satellites are a transitory phenomenon. Similar conclusions are drawn by the Gillet et al (2015) analysis of CLUES (Constrained Local UniversE Simulations). The planes they find contained 11 satellite galaxies at most, indicating the likely possibility of M31's plane of 15 satellites being an extreme occurrence.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the general conclusion is that planes of satellites are a transitory phenomenon. Similar conclusions are drawn by the Gillet et al (2015) analysis of CLUES (Constrained Local UniversE Simulations). The planes they find contained 11 satellite galaxies at most, indicating the likely possibility of M31's plane of 15 satellites being an extreme occurrence.…”
Section: Introductionsupporting
confidence: 82%
“…About a third of satellites have high velocities that are perpendicular to the planar formation, making their presence in the plane purely coincidental. Gillet et al (2015) conclude that the observed satellite planes appear to be in agreement with the ΛCDM but as a transitory feature, created with a few planar satellites and several timely interlopers. Such coincidental placement of galaxies may reduce the number of observed kinematically coherent planes.…”
Section: Introductionmentioning
confidence: 60%
“…The member satellites rotate about M31 in the same sense. The reality and probability of this plane has been discussed at length, especially with regard to whether such a structure is consistent with galaxy formation in a ΛCDM cosmology (see, e.g., Hammer et al 2013;Bahl & Baumgardt 2014;Ibata et al 2014;Pawlowski et al 2014;Buck et al 2015;Gillet et al 2015;Libeskind et al 2015;Phillips et al 2015). Collins et al (2015) have investigated the possibility that inplane galaxies and off-plane galaxies may have formed and evolved differently.…”
Section: Quenching By Reionization?mentioning
confidence: 99%
“…Both objects reionized in isolation relative to each other: their patches are easily identified and disconnected. Ocvirk & Aubert (2011) and Gillet et al (2015) predicted that this kind of reionization should lead to a more extended radial distribution of their satellites at z=0 compared to models without radiative transfer. The LG also reionized in isolation from the large-scale environment, as no ionization fronts appeared to sweep across them from outside.…”
Section: The Local Groupmentioning
confidence: 99%